Digestibility, Blood Metabolites, Faecal Bacterial Population and Performance of Madura Cattle Inoculated with Cellulolytic Bacteria Consortium - Firkani, Rahmatiana Widi; Suharti, Sri; Astuti, Dewi Apri (Jurnal Sain Peternakan Indonesia, 2024)
This study aimed to evaluate the effect of cellulolytic bacteria consortium inoculation on digestibility, blood metabolites, fecal microbial population, and performance, of Madura cattle. This study used 15 Madura cattle with an initial body weight of 150-300 kg with a standard deviation of 38.45 kg. A complete group randomized design with 3 treatments and 5 replications was used in this study. The grouping of the cattle is based on initial body weight. The treatments consisted of T1: concentrate: rice straw with a ratio of 50:50 as the control ratio, T2: T1 + 5 ml 106 CFU/ml of cellulolytic bacteria consortium, and T3: T1 + 10 ml 106 CFU/ml cellulolytic bacteria consortium. The data obtained were analyzed using analysis of variance (ANOVA) and the differences among treatments were further analyzed using Duncan's multiple range test. The result showed that inoculation of cellulolytic bacteria consortium until 106 CFU/ml had no significant effect on performance, blood metabolites, digestibility, and total microbial population during 30 days of treatment. In conclusion, inoculation of cellulolytic bacteria consortium did not improve performance and digestibility in short periods and did not interfere with blood metabolites.